Too much happiness [compact disc, unabridged] : stories - Munro, Alice, 1931- (Random House Audio, 2009)
Tackling a variety of themes, such as love, loss, and redemption, author Alice Munro delivers a masterfully crafted collection of short stories. In the title story, Too Much Love, Sonia Kovalevsky, a Russian bohemian, embarks on a winter-long journey across Europe with her love, discovering that love and monogamy are exactly the perfect match.